Meckel’s Diverticulum: The “Great Mimic” but Often a Forgotten Cause of Acute Abdomen during Pregnancy - Beatriz Féria; Madalena Trindade; Maria João Palma; Joana Figueiredo; Filipa Passos (Case Reports in Obstetrics and Gynecology)
Meckel’s diverticulitis is an extremely rare event during pregnancy. Its diagnosis is often difficult and can result in higher maternal and fetal morbimortality. We describe a case of a 40-year-old healthy pregnant woman at 33 weeks of gestation who presented with abdominal pain and tender abdomen, leukocytosis, and elevated PCR. The imagiological exams were not conclusive. After an urgent caesarean section due to worsening of clinical status and nonreassuring fetal well-being, a laparotomy revealed a distended, necrotic, and perforated Meckel’s diverticulum.